QMorphoStream: processing tools in QGIS environment for the quantitative geomorphic analysis of watersheds and river networks - Tebano, Carlo; Pasanisi, Francesco; Grauso, Sergio (Earth science informatics, 2017)
The quantitative geomorphic analysis is a powerful tool for the study of geomorphology and landforms, as it provides objective methods to describe the main properties of drainage basins by means of an appropriate set of parameters. Over the last decades, GIS techniques and processing tools have been widely applied to the geomorphic analysis, and specific applications were developed, essentially using commercial software. In the present paper, the first experimental version of QMorphoStream, an originally developed set of processing tools for quantitative geomorphic analysis in QGIS environment, is presented. Besides the obvious advantage in terms of cost reduction, the choice of an open source development environment allowed us to integrate original algorithms with both QGIS built-in functions and processing tools available in the developers’ community.